2020
DOI: 10.18203/2349-2902.isj20200825
|View full text |Cite
|
Sign up to set email alerts
|

Is there a need for antibiotic cover in clean surgery like laparoscopic cholecystectomy: a prospective study

Abstract: Background: Even with a low post-operative infection complication rate in elective laparoscopic cholecystectomy (LC), most surgeons use prophylactic antibiotics out of habit. This prospective study was done to analyze the need for such prophylaxis in cases of elective LC.Methods: 135 successive patients undergoing elective LC were included in the study. Patients were randomized into 3 groups. Group A (n=45) cases received 3 doses of injection ceftriaxone in the post op period, group B (n=48) cases received a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The author suggested that in a clean case of cholelithiasis, whether it's single or 3 doses ABP, it should be stopped. 34 Development of SSI in case of positive bile culture, bile and/or stones spillage due to intraoperative gallbladder perforation is still a controversial topic. 24 Uludag et al reported no relationship between the organisms isolated from the bile and the subsequent SSI.…”
Section: On the Other Hand Those Who Are In Support Of Abp Argue Thatmentioning
confidence: 99%
“…The author suggested that in a clean case of cholelithiasis, whether it's single or 3 doses ABP, it should be stopped. 34 Development of SSI in case of positive bile culture, bile and/or stones spillage due to intraoperative gallbladder perforation is still a controversial topic. 24 Uludag et al reported no relationship between the organisms isolated from the bile and the subsequent SSI.…”
Section: On the Other Hand Those Who Are In Support Of Abp Argue Thatmentioning
confidence: 99%